The essence of chocolate : recipes for baking and cooking with fine chocolate - Scharffenberger, John.; Steinberg, Robert; Spivack, Ann Krueger; Heller, Susie; Scharffen Berger Chocolate Maker (Firm) (New York : Hyperion, 2006)
Provides over one hundred recipes and cooking tips involving chocolate, ranging from "intensely chocolate" to "a hint of chocolate," along with a history of chocolate, chocolate farming, and the origins of the Scharffenberger chocolate business.
Introduction: A Note from Susie Heller -- Favorite Techniques -- Melting Chocolate -- Chocolate Curls and Shavings -- Lining a Baking Sheet with Parchment -- Baking in a Water Bath -- Rotating Baking Pans in the Oven -- Using Ramekins and Souffle Molds -- Favorite Kitchen Tools -- Using Scharffen Berger Chocolate in Your Own Recipes / Alice Medrich -- Before We Made Chocolate -- From Medicine to Chocolate: Robert Steinberg -- Living with an Illness -- From Winemaking to Chocolate: John Scharffenberger -- Flavor as a Dynamic Experience -- Intensely Chocolate -- That Chocolate Cake -- Chocolate Almond Cake -- Orbit Cake -- Chocolate Pudding Cakes -- Chocolate Chocolate Cupcakes -- Baked Hot Chocolate -- Molten Cakes -- Chocolate Orange Fondue -- Quick Fix: Chocolate and Olive Oil Fondue -- Orange Chocolate Ganache Tart -- Chocolate Pecan Pie -- Chocolate Mousse -- Dark Chocolate Ice Cream -- Quick Fix: Ice Cream Shooters -- Chocolate Sorbet -- Cocoa Ice Bars -- Fudgy Brownies -- Cakey Brownies -- Chocolate Drop Cookies -- Chocolate Crinkle Cookies -- Chocolate Shortbread with Cacao Nibs and Sea Salt -- Quick Fix: Chocolate-Dipped Potato Chips and Pretzels -- Robert's Truffles -- Tempering Chocolate -- Scotch Truffle Hearts -- Fudge -- Factory Store Hot Chocolate -- Chocolate Liqueur -- Chocolate Martini -- John's Classic Drinking Chocolate -- A New American Chocolate Company -- What Is Chocolate Liquor? -- Kitchen Chocolate -- Essentially Chocolate -- Chocolate Chunk Cheesecake -- Cocoa Chiffon Cake -- Chocolate Chinchilla -- Chocolate Roulade -- Quick Fix: Sofia's Almond, Fig, and Chocolate-Shaving Sandwich -- One-Pot Sour Cream Cake -- Chocolate Souffle -- Chocolate Pecan Tart -- Orange Chocolate Baklava -- Chocolate Ginger Pots de Creme -- Black and White Creme Brulee -- Chocolate Zabaglione Trifle -- Chocolate Peanut Butter Gianduja -- Quick Fix: Chocolate and Peanut Butter Panini -- Silky Chocolate Pudding -- Frozen Chocolate Mousse -- Bailey's Milk Chocolate Truffles -- Chocolate Biscotti -- TKOs -- Quick Fix: Chocolate Platter with Fruit and Nuts -- Chocolate Chunk Cookies -- Ultra-Thin Chocolate Chunk Cookies -- PB & C Cookies -- Cocoa Cabanas -- S'mores -- Chocolate Smooches -- Brown Butter Blondies -- Quick Fix: Toasted Coconut Clusters -- Chocolate Caramels -- Chocolatte -- Robert's Egg Cream -- How We Make Our Chocolate -- The Bean Cleaner -- The Roaster -- The Winnower -- The Melangeur -- The Conche/Refiner -- The Tempering Machine -- The Molding Machine -- A Hint of Chocolate -- Chocolate-Marbled Gingerbread -- White Velvet Cake with Milk Chocolate Ganache -- Layered Crepe Torte -- Banana Caramel Cake -- Quick Fix: Bread and Chocolate -- Pull-Apart Kuchen -- Chocolate Chunk Challah -- Chocolate Chunk Muffins -- Chocolate Chunk Scones -- Mascarpone-Stuffed French Toast -- Cacao Nib Waffles -- Quick Fix: Oatmeal with Nibs -- Brown Sugar Meringue Bars -- Polvorones -- Cacao Nib Macaroons -- Apricot Hazelnut Squares -- Lace Cookies -- Mini Madeleines -- Cocoa Caramel Panna Cotta -- Mint-Basil Chocolate Chunk Ice Cream -- Quick Fix: Pepper Mill Nibs -- Pumpkin Seed Nib Brittle -- Almond Roca -- Cocoa Nuts -- Chocolate Banana Milkshake -- Roasted Squash with Nib Vinaigrette -- Quick Fix: Goat Cheese with Nibs -- Spinach and Walnut Salad with Pears and Nib Vinaigrette -- BBQ Sauce -- Tortilla Soup -- Three-Bean Chili -- Quick Fix: John's Cocoa Rub -- Chile-Marinated Flank Steak -- Baked Beans -- Cacao -- An Understory Tree -- The Bitter Seeds -- A Vulnerable Crop -- Cultivating Cacao -- A Closer Look at Fermentation -- The First Taste of Cacao -- The Three Types of Cacao -- A Closer Look at Cacao Genetics -- The Forest Garden -- Cacao's Need for the Biting Midge -- The Meaning of the Percent Sign -- Why We Also Make Single-Origin Chocolates -- Basics and Add-Ons -- Citrus Sugar -- Marshmallows -- Honeycomb -- Creme Fraiche -- Clarified Butter -- John's Simple Chocolate Sauce -- Hot Fudge Sauce -- Chocolate Syrup -- Dulce de Leche -- Custard Sauce -- Macerated Berries -- Candied Almonds -- Whipped Cream -- The Future of Cacao -- Ecuador -- The Dominican Republic -- Guatemala -- Panama -- A New Chapter for Scharffen Berger Chocolate Maker -- Glossary of Chocolate-Related Terms.
At head of title: Scharffen Berger Chocolate Maker.
Includes index.
Includes bibliographical references (pages 362-367) and index.
Keywords: Cooking (Chocolate); Chocolate; Desserts; Chocolate; Cooking (Chocolate); Desserts; Cooking -- Chocolate; Nonfiction